2013
DOI: 10.1111/joic.12037
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Revascularization: A Systematic Review of the Evidence

Abstract: CAS represents a safe and effective stroke prevention strategy in high surgical risk patients when compared with CEA. The inconsistent results from the RCTs and the improved outcomes in the prospective clinical trials are likely related to variability in operator experience, use of embolic protection devices, and patient selection strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…After the first phase of the selection process, 26 records were included for the second phase assessment. After reading all full texts, 17 SRs were included8–24 and 9 SRs were excluded with reasons 25–33. Reasons for exclusions at the second phase are presented in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…After the first phase of the selection process, 26 records were included for the second phase assessment. After reading all full texts, 17 SRs were included8–24 and 9 SRs were excluded with reasons 25–33. Reasons for exclusions at the second phase are presented in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the risk of readmission is likely driven in part by patient selection. Currently, CEA is the mainstay treatment of symptomatic and asymptomatic carotid artery stenosis, and CAS is typically reserved for patients with comorbidities or anatomy that put them at increased risk for adverse outcomes following CEA (1,15,16). Nevertheless, the risk of readmissions for CAS was higher than CEA even after accounting for observed differences in patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, studies have found the long-term risk of all strokes (major and minor) to be significantly higher for CAS than CEA, 39,40 with incidence rates reported to range from 7.9% to 10.1% for CEA and 9.0% to 14.2% for CAS. 38 A few trials have also reported a significantly higher rate of stroke in the periprocedure period for CAS, [39][40][41] although this risk may be mitigated by the use of embolic protective devices during stenting. 38 Acute thrombosis is a catastrophic event that requires immediate recognition and treatment with thrombolysis, endovascular thrombosuction, or open surgery.…”
Section: Thrombosis and Thromboembolismmentioning
confidence: 99%
“…38 A few trials have also reported a significantly higher rate of stroke in the periprocedure period for CAS, [39][40][41] although this risk may be mitigated by the use of embolic protective devices during stenting. 38 Acute thrombosis is a catastrophic event that requires immediate recognition and treatment with thrombolysis, endovascular thrombosuction, or open surgery. 42 The most frequently cited causes of acute thrombosis after CAS are failure to receive antiplatelet medication and technical failure, such as stent malposition and carotid dissection.…”
Section: Thrombosis and Thromboembolismmentioning
confidence: 99%